2009
DOI: 10.4021/gr2009.12.1331
|View full text |Cite
|
Sign up to set email alerts
|

A Case of O1 Vibrio Cholera Bacteremia and Primary Peritonitis in a Patient With Liver Cirrhosis

Abstract: Vibrio cholerae are Gram-negative bacteria that are differentiated into O1/O139 and non-O1/non-O139 serogroups depending on their ability to agglutinate with specific antiserum. In contrast to non-O1/non-0139 Vibrio cholerae, which are more prone to invade the bloodstream, Vibrio cholerae O1 is rarely the cause of bacteremia. We report a case of O1 Vibrio cholera bacteremia and primary peritonitis in a patient with liver cirrhosis. The literature on the subject is also reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Previous studies in Bepanda, Douala (Cameroon) have reported the absence of V. cholerae O1 in environmental samples [18, 19] which is contrary to our findings. However, similar patterns of low prevalence of V. cholerae O1 in environmental samples comparable to what was found in this study have been reported in Haiti [2022]. The pathogen has been found to thrive best in saline environments but can also survive in low saline environment provided the environment is warm and has adequate organic nutrient [23].…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies in Bepanda, Douala (Cameroon) have reported the absence of V. cholerae O1 in environmental samples [18, 19] which is contrary to our findings. However, similar patterns of low prevalence of V. cholerae O1 in environmental samples comparable to what was found in this study have been reported in Haiti [2022]. The pathogen has been found to thrive best in saline environments but can also survive in low saline environment provided the environment is warm and has adequate organic nutrient [23].…”
Section: Discussionsupporting
confidence: 88%
“…Although these non-O1 strains lack epidemic or pandemic potential, some isolates have been reported to possess cholera toxin ( ctx ) gene and other virulence genes [25] present in O1 serogroup. Although we did not further investigate the non-O1 isolates for virulence determinants, their presence in our study area should be considered of public health importance and should not be ignored particularly as they have occasionally been isolated from cases of cholera-like diarrhoea [26] and from a variety of extra intestinal infections [27]. In samples where the pathogen was not recovered, it could that either the prevailing environmental conditions in their niche were unfavorable for growth of V. cholerae or the source was regularly disinfected (wells and taps).…”
Section: Discussionmentioning
confidence: 99%
“…Immunocompromised status and prematurity have also been addressed as risk factors. [4][5][6][7][8][9][10] In our case, the patient had leukemia, chemotherapy, damaged mucosal barriers and associated infection with E. coli as predisposing factors. The patient did not have any history of travel or any episode of diarrhea prior to current admission.…”
Section: Discussionmentioning
confidence: 66%
“…The limited reported cases of invasive disease caused by V. cholerae O1 are summarized in Table 1. [4][5][6][7][8][9][10] Pathogenic mechanisms causing invasion in V. cholerae infections are not well recognized. Possible reasons could be pre-existing disruption of mucosal barrier, achlorhydria, simultaneous infection with an invasive pathogen, translocation of viable V. cholerae via M cells and hemolysin production.…”
Section: Discussionmentioning
confidence: 99%